Experimental Investigation for Non and Partially Composite Cold-Formed Steel Floor Beams - Tuka Mohammed Qasim; Salah Rohaima Al-Zaidee (Salehan Institute of Higher Education, 2019)
In this study, six full-scaled models of RC floors supported by cold-form steel sections have been tested. Each model consists of RC 75mm thick slab supported on two parallel cold-formed steel beams with a span of 3m and spacing of 500mm. The slab has an overhang part of 250mm on each side. In the first and fourth models, the slab has been casted directly on the top flanges with no shear connector to simulate the effectiveness of friction in resisting of the lateral-torsional buckling. Shear studs have been drilled in the second and fifth models to ensure the composite action. Finally, the flanges have been embedded for the third and sixth models. A single channel beam is used in the first, second, and third models while a built-up beam is used in the fourth, fifth, and sixth models. Each model has been loaded up to failure under a pure bending with two-line loads located at the third points. Data for loads, deformations, and strains have been gathered. Except the fourth and the sixth models that failed in local buckling modes, all other models failed in global lateral-torsional buckling modes. For the single beam models; the load carrying capacity of the non-composite model is 82.9% less than the capacity of the composite models with shear studs and embedded flange. For the built-up models; the load carrying capacity of the non-composite model is 44.2 % less than the loads of the composite model with shear stud and 48.7% less than the model with the embedded flange.